Peningkatan Efisiensi Pengelolaan Stok Barang dan Pencatatan Keuangan melalui Pengabdian Masyarakat di PT Mega Tiara Sinar Abadi - I Kadek Bagiana; Theresa Febrianti Nasam (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
This community service activity discusses efforts to increase efficiency in managing inventory and financial records at PT Mega Tiara Sinar Abadi, Cabang Gunung Agung, Bali. This company needs help with stock management, which requires time-consuming manual stock-taking. This activity involved initial evaluation, employee training and the use of information technology in stock taking. Stock-taking training has been provided to employees, which has resulted in increasing their understanding of this process. With scan tools and software, stock-taking can be done quickly and accurately. The result was better operational efficiency, more controlled stock management, and increased accuracy of financial reports. Trained employees also assist the company in maintaining stakeholder trust and creating a culture of continuous improvement in stock management. The implementation of this community service activity was successful, showing that collaboration between academia and industry provides significant benefits.